Mediatization of Islam; The Case of The Indonesian Muslims In Hungary - Hazim Hazim; Nurul Musdholifah (The Journal of Society and Media, 2021)
This article addresses mediatization of religion which particularly focuses on how Indonesian Muslims in Hungary mediatize their Islamic practices. It is a result of an empirical study incorporating two approaches, qualitative and quantitative methods. Participant observation and semi-structured in-depth interviews involving 18 informants were conducted for collecting the quantitative data whereas the quantitative data was generated from an online survey collected from 102 participants (60 males and 42 females). The result of the study shows that the lack of integration to the local Islamic institutions affects the mediatization of Islam. The form of Islamic mediatization can be seen through their way of obtaining religious messages, news, and information which primarily relies on the internet. Most of them depend on Social media, where YouTube channel was the most favorite one followed by Facebook and Instagram,  to obtain Islamic resources. The dependency upon media particularly YouTube has the potential to shift religious authority from institutional to individual authority. While some scholars debate whether mediatization of religion could encourage secularization or not, the case of Indonesian Muslims in the Hungarian context shows that instead of becoming more secular, the dependency upon media for religious practices affects them to be more religious.